Emerging non-canonical functions for heterotrimeric G proteins in cellular signaling. (June 2013) - Ahmed, Syed M.; Angers, Stephane
Abstract Classically heterotrimeric G proteins have been described as the principal signal transducing machinery for G-protein-coupled receptors. Receptor activation catalyzes nucleotide exchange on the Gα protein, enabling Gα-GTP and Gβγ-subunits to engage intracellular effectors to generate various cellular effects such as second messenger production or regulation of ion channel conductivity. Recent genetic and proteomic screens have identified novel heterotrimeric G-protein-interacting proteins and expanded their functional roles. This review highlights some examples of recently identified interacting proteins and summarizes how they functionally connect heterotrimeric G proteins to previously underappreciated cellular roles.